PRINSIP-PRINSIP MANAJEMEN ISLAM PADA LEMBAGA PENDIDIKAN DALAM SEJARAH PERADABAN ISLAM - Ismah (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
Management is a crucial aspect of the sustainability and success of educational institutions. In the history of Islamic civilization, the management of educational institutions developed based on principles rooted in Islamic values, such as trust (amanah), justice, consultation (shura), and responsibility. This article aims to examine the principles of Islamic management as applied in educational institutions throughout the history of Islamic civilization and to analyze their relevance to the management of contemporary Islamic educational institutions, particularly Madrasah Ibtidaiyah. This study employs a qualitative approach using a literature review method of classical and contemporary sources that discuss the history of Islamic education and educational management. The findings indicate that Islamic management principles were systematically implemented in classical Islamic educational institutions such as kuttab and madrasah, contributing to the development of a strong scholarly tradition and an advanced civilization. These principles remain relevant and can serve as a foundational framework for the management of modern Islamic educational institutions.